Penerapan Hukum Ekonomi Kerakyatan Syariah Sebagai Fundamental Pertahanan Negara Indonesia - Muhamad Afifullah; Irwan Triadi (Pusat Riset dan Inovasi Nasional, 2023)
The state is obliged to defend its territory from annexation, but it also targets the economic sector with the aim of weakening the domestic and sovereign government. Many people are trapped by the interest system adopted in conventional co-operatives, because it causes disintegration between the rich and the poor. Gradually, the large gap can threaten the internal state. It also affects the rate of business productivity which is increasingly hampered, due to the substitution of domestic products by foreigners. The research uses descriptive analysis method with qualitative research type and literature study approach. The results of this study are Islamic economics and conventional people's economy have similarities, namely helping and mutual cooperation and differences in the existence of interest, while in Islamic economics using profit sharing and margins. Then the sharia people's economy can be applied as a defence of the country's economy through legislation. In order to maximise the potential of the Islamic people's economy, development is carried out on human resources and the productive sector of small and micro medium enterprises, as well as policies to limit exports and imports of products.